Hellinsia mongolica - Ustjuzhanin, P. Ya.; Kovtunovich, V. N. (Zenodo, 2018)
Hellinsia mongolica (Zagulajev et Pentschukowskaya, 1972) MATERIAL EXAMINED. Khakhassia: Azrakov, 22.VI 2010, 1♀ (R. Yakovlev). DISTRIBUTION. The mountains of South Siberia, Mongolia, Yakutia, China. Published as part of Ustjuzhanin, P. Ya. & Kovtunovich, V. N., 2018, The fauna of plume moths (Lepidoptera: Pterophoridae) of the Republic of Khakassia, pp. 21-24 in Far Eastern Entomologist 362 on page 23, DOI:10.25221/fee.362.4, http://zenodo.org/record/7168479